2014
DOI: 10.3109/08941939.2014.987407
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Treatment of Acute Liver Failure with Adipose Derived Stem Cells

Abstract: The intravenous injection of allogenic ASCs in this model of CCl4-induced liver failure reduced the mortality in treated animals. ASCs injected in the rat tail vein were found in the liver in animals with induced acute liver failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
1
8
0
2
Order By: Relevance
“…Considerably, compared with those without ADSC injection, less incidences of inflammatory infiltration were appeared around the liver central vein of treated mice after tail intravenous injection of the SPIONs cluster@PDA-labeled ADSCs for 24 hrs, implying that the labeled ADSCs could promote the repair of injured liver. These results are in well consistent with the previous studies that unlabeled ADSCs can ameliorate the liver injuries induced by CCl 4 in rodent model 39 40 41 42 . Hence, above data indicate the therapeutic effects of ADSCs on liver injures cannot be affected by the labeling of SPIONs cluster@PDA nanoparticles, and also proved the good biocompatibility of these nanoparticles.…”
Section: Resultssupporting
confidence: 93%
“…Considerably, compared with those without ADSC injection, less incidences of inflammatory infiltration were appeared around the liver central vein of treated mice after tail intravenous injection of the SPIONs cluster@PDA-labeled ADSCs for 24 hrs, implying that the labeled ADSCs could promote the repair of injured liver. These results are in well consistent with the previous studies that unlabeled ADSCs can ameliorate the liver injuries induced by CCl 4 in rodent model 39 40 41 42 . Hence, above data indicate the therapeutic effects of ADSCs on liver injures cannot be affected by the labeling of SPIONs cluster@PDA nanoparticles, and also proved the good biocompatibility of these nanoparticles.…”
Section: Resultssupporting
confidence: 93%
“…(3) ERC-treated group: mice first receiving i.p. injection of CCl 4 were injected intravenously with 1 × 10 6 ERCs at passage 4 resuspended in 200 μl of PBS 30 min later [ 23 ]. Mice were sacrificed 24 h after injection of CCl 4 , and blood was collected.…”
Section: Methodsmentioning
confidence: 99%
“…It is assumed that the application of stem cells obtained from stromal vascular fat tissue accelerates the regenerative process by allowing for improved angiogenesis and modulation of inflammation, as has been previously observed in animal-model studies ( 14 , 15 ); however, to the best of our knowledge, this has not been demonstrated in direct connection with ALPPS approach and Sus scrofa model organism. The aim of the present study was to identify candidate genes that may be used as screening markers for monitoring the process of liver regeneration following the first stage of ALPPS.…”
Section: Introductionmentioning
confidence: 92%